Imagining the Atacama Desert : A Five-Hundred-Year Journey of Discovery - Francaviglia, Richard V. (Book collections on Project MUSE., 2018)
"Widely regarded as the driest place on earth, the seemingly desolate Atacama Desert of Chile is a place steeped in intrigue and haunted by collective memories. This book, based on archival research and the author's personal field work, brings together the works of geographers, historians, anthropologists, botanists, geologists, astronomers, novelists, and others to offer a nuanced understanding of this complex desert landscape. Beginning with the indigenous Atacameño peoples at the southern edge of the Incan Empire, the volume moves through five hundred years of history, sharing accounts written by Spanish, French, German, Dutch, British, American, and other travelers pirates, scientists, explorers, and entrepreneurs among them. The Atacama's austere landscape hides many secrets, including vast mineral wealth, the world's oldest mummies, and the more recent remains of dissidents murdered by the regime of former Chilean dictator Augusto Pinochet in the early 1970s. Today numerous observatories operate under the Atacama's clear night skies, astronauts train on the rugged desert floor, and tourists flock there for inspiration. In addition to a rich set of narratives, the book features 115 images historical maps, photographs, and natural history illustrations, most in full color to tell a more complete and compelling story. Imagining the Atacama Desert shows how what was once a wilderness at the edges of empire became one of South America's most iconic regions, one that continues to lure those seeking adventure and the unknown"--Provided by publisher.